Are rural American Indian adolescents becoming a race of angels? - Cournane, John (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
This article discusses the importance of identity formation and the development in young Aboriginal persons as important in the early years of education. Education is an important anchor that would help ensure a reduction in adolescent suicides and improve ego development.